POTENTIAL STUDY OF FREE LIVING NITROGEN FIXING BACTERIA IN VARIOUS USES IN KAYU TANAM VILLAGE MANDOR SUBDISTRICT LANDAK REGENCY - Fitriani, Adelia; Nusantara, Rossie Wiedya; Gafur, Sutarman (Fakultas Pertanian Universitas Tanjungpura, 2025)
Nitrogen is an essential macronutrient required for plant growth and development. In its gaseous form (Nâ‚‚), which is abundant in the atmosphere, nitrogen cannot be directly utilized by plants. Therefore, nitrogen fixation is needed to convert it into available forms such as ammonium (NHâ‚„âº) and nitrate (NOâ‚ƒâ»). â‚ƒâ»). The population of Azotobacter sp. in soil can be affected by land use types. This study aimed to examine the potential of free-living nitrogen-fixing bacteria in different land uses in Kayu Tanam Village, Mandor Subdistrict, Landak Regency. Soil samples were collected from this village and analyzed at laboratories in the Faculty of Agriculture, Universitas Tanjungpura. The study was conducted from February to April 2025. Samples were taken diagonally from five points per site, with 50 m between points. Composite samples were taken 20 m from the center point. Observed parameters included bacterial population, potential, and characterization, pH, organic carbon, total nitrogen, C/N ratio, bulk density, moisture content, and soil temperature. Results showed the highest population in secondary forest (62.80 Ã— 10âµ CFU/g) and the lowest in oil palm land (46.20 Ã— 10âµ CFU/g). Secondary forest had six Azotobacter sp. types, indicating its high potential for nitrogen fixation.